Convergence in the Spanish and Portuguese NUTS 3 regions: An exploratory spatial approach - Miguel Viegas; Micaela Antunes (Intereconomics, 2013)
Since their accession to the European Union in 1986, both Portugal and Spain have benefited from strong financial support. Both countries have experienced considerable growth in income per capita, converging towards average European levels. However, several studies suggest a high degree of persistence of regional asymmetries within the countries. This paper empirically analyses convergence among NUTS 3 regions of the Iberian Peninsula between 1995 and 2008. The results reveal divergent national trends and indicate no evidence of catching-up effects among the poorest regions, confirming the existence of economic clusters.
Keywords: 330; Regionale Disparität; Regionale Entwicklung; Entwicklungskonvergenz; Spanien; Portugal